Driving The Operation of the Nurse Collaboration Center in COVID-19 Outbreak - Sathira-Angkura, Teeraporn; Leelawong, Silima; Amonprompukdee, Attaya; Janta-Um-Mou, Uraiporn (Journal of The Royal Thai Army Nurses, 2021)
COVID-19 is a global outbreak, a new emerging disease causing a dramatically increased the number of infected patients continually, result in overload working of the health personnel particularly nurses. Good management of the country is quite important and the Ministry of Public Health has concerned of nursing management. Consequently, the nurse collaboration center in COVID-19 outbreak was established to formulate policy, direction, and collaboration among nurses as a country agency. The nurse collaboration center has been working through the chief nursing officers (CNOs) committee, in which consisted of CNOs from regional and central sectors over the country. The 4 phrases of driving the nurse collaboration center: the 1St phase; 1-2 months of the beginning outbreak, the 2nd phase; 3-5 months after the outbreak, the 3rd phase; 6-10 months after the outbreak, and the 4th phase; 11-12 months after the outbreak. The operation of the nurse collaboration center revealed 3 major impacts on nursing profession and population: 1) policy formulation and direction of nursing service management, 2) a notable supervision, monitoring and collaboration mechanism system, and 3) various nursing knowledge and technology development. In addition, the policy recommendations were proposed to the Ministry of Public Health and the Nursing Organizations to better prepare the readiness for further nursing service management in the next wave of COVID-19 outbreak.